Mengkaji Nilai-Nilai Moral dalam Puisi sebagai Media Pendidikan Moral - Siti Sumarsilah (IKIP Budi Utomo Malang, 2017)
Poem is always made as a facility to express emotional exclamation and idealism. The emotional voice and idealism expressed through poem, of course are balanced with moral exclamation either directly or symbolically. To recognize moral values in poems, readers have to recognize characteristics and styles user by poets in expressing their emotional exclamation and idealism. In addition, the readers’ approach anf paradigm as a meaning breaker which interprets moral values in poems are also very inﬂuential. The determinism and indeterminism views in theology can be used as a paradigm to understand universally moral values.